2001
DOI: 10.1111/j.1553-2712.2001.tb00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Young Adults Who Present to the Emergency Department with Chest Pain

Abstract: Abstract.Background: Most studies of emergency department (ED) chest pain patients exclude patients <30-40 years old. As a result, the clinical course of these patients is poorly described. Objective: To study the clinical characteristics, hospital course, and 30-day outcomes of ED chest pain patients <40 years old. The hypothesis was that patients <40 years old without a cardiac history and with normal electrocardiograms (ECGs) or no cardiac risk factors would be at a <1% risk for acute coronary syndromes (AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
16
0

Year Published

2001
2001
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 21 publications
5
16
0
Order By: Relevance
“…This is consistent with the rates of 2.1% and 4.7%, respectively, found in previous descriptions of young adults with 15,20 In our subgroup analyses, the overall rate of ACS was somewhat higher than that described by Walker et al, but the ACS rates were all ,2%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with the rates of 2.1% and 4.7%, respectively, found in previous descriptions of young adults with 15,20 In our subgroup analyses, the overall rate of ACS was somewhat higher than that described by Walker et al, but the ACS rates were all ,2%.…”
Section: Discussionsupporting
confidence: 93%
“…[5][6][7][8][9][10][11][12][13] A previous study looked at the clinical characteristics and 30-day outcomes of patients younger than 40 years of age and attempted to define a clinical decision rule for patients at ,1% risk for adverse CV events. 15 We examined this decision rule in a larger cohort of patients approximately twice the size of the above-stated study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because female patients are more likely to present with atypical symptoms of ACS, we expected that female sex, rather than male sex, would be associated with avoidable CPOU utilization. 1921 However, our findings are consistent with a large body of literature demonstrating that men are more likely than women to receive testing for ACS. 2226 Chest pressure, vomiting, and lightheadedness may be associated with increased avoidable CPOU placement because physicians may consider these features concerning for ACS and therefore increasing their likelihood of CPOU utilization.…”
Section: Discussionsupporting
confidence: 90%
“…[1][2][3] Two articles in this issue of Academic Emergency Medicine attempt to further answer the question of which chest pain patients we can send home. The study by Walker et al 4 addresses the issue of whether younger patients without cardiac history, risk factors, and ECG abnormalities are truly at low risk for adverse cardiovascular events. In the 16-month study period, the authors prospectively identified and followed 487 patients between the ages of 24 and 39 years presenting to a university ED with non-cocaine-related chest pain.…”
mentioning
confidence: 99%